A low-loss, high-impedance manganese-zinc ferrite material and a preparation method thereof
By using PVA granulation, presintering and crushing methods in the preparation process of manganese-zeb ferrite materials, combined with low-temperature vacuum hot-pressure sintering and air pressure-free resintering, the magnetic conduction of existing materials at high frequency is solved. The problem of insufficient rate and impedance achieves low loss and high impedance material performance, and is suitable for medium and high frequency anti-electromagnetic interference devices.
Patent Information
- Application Number
- CN202310715778.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-15
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2043-06-15
AI Technical Summary
Existing manganese-zeb ferrite materials are difficult to meet the needs of high permeability and high impedance at high frequencies, and are highly manufactured and complex in processes, resulting in limited application.
By using PVA granulation, presintering and crushing methods in the preparation process, combining low-temperature vacuum hot-pressure sintering and air pressure-free resintering, the component uniformity and performance of the material are optimized.
It realizes low loss and high impedance manganese-zeb ferrite materials, suitable for medium and high frequency anti-electromagnetic interference devices, reducing manufacturing costs and process complexity.
Smart Images

Figure CN116969752B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of soft ferrites, and in particular to a low-loss, high-impedance manganese-zinc ferrite material and a preparation method thereof. Background Art
[0002] Manganese-zinc ferrite is actually a single-phase solid solution, which is composed of spinel-structured manganese ferrite, zinc ferrite, and a small amount of ferroferric oxide. Manganese-zinc ferrite materials can be used to make solenoid valves, magnetic heads, switches, magnetic fluids, and can also be used in magnetic recording media, magnetic resonance imaging, catalysts and other devices. It is very widely used. Manganese-zinc ferrite is the most important material in soft ferrite materials. Its output is very large, almost accounting for more than the total production of soft ferrite materials.
[0003] In the electronic information age, with the rapid development of communication satellites, mobile communications, and computer applications, the impact of electromagnetic interference (EMI) in the military and civilian electronic information fields has become increasingly serious, causing great harm to the public environment, personal safety, and information confidentiality. An effective way to solve electromagnetic pollution and improve the ability of electronic equipment to resist electromagnetic interference is to adopt electromagnetic compatibility (EMC) design, which requires a large amount of anti-electromagnetic interference materials. With the miniaturization and high-frequency development of electronic equipment, there is an urgent need to have electronic materials with high magnetic permeability and high impedance at high frequencies. Compared with NiZn ferrite, MnZn ferrite has low resistivity and high dielectric constant, which makes it difficult to adapt to high frequencies above 1MHz. Therefore, most devices used at frequencies above 1MHz are NiZn ferrite materials. However, NiZn materials have high manufacturing costs, low magnetic permeability and impedance in the low-frequency band, and their applications are also subject to certain restrictions. Iron-poor MnZn ferrite materials have high magnetic permeability in the low-frequency band, and high resistivity, so their impedance in the high-frequency band is also high. Compared with NiZn materials, its manufacturing cost is also low, and it can replace part of NiZn materials and be used in the production of medium and high frequency anti-electromagnetic interference devices.
[0004] Through the existing technology and literature search, it was found that the patent document (CN111233452B) discloses a high-frequency and high-impedance iron-poor manganese-zinc ferrite and a preparation method thereof. The raw materials include a main component and an additive. The main component includes 47.8-49.8% Fe2O3, 31-36% MnO, 15-18.5% ZnO and 0.7-2% Co2O3 in molar percentage; the additive includes 10-100ppm SiO2, 200-1000ppm CaCO3, 100-300ppm Bi2O3, 100-300ppm ZrO2 and 100-600ppm TiO2.
[0005] The patent document (CN108147805B) discloses a method for preparing manganese-zinc ferrite, which includes the following steps: providing and mixing Fe2O3, Mn3O4, ZnO, CoO, NiO and CuO powders to obtain a first mixed powder; performing a first ball milling on the first mixed powder to obtain a second mixed powder; performing a first sintering treatment on the second mixed powder to obtain a first block; crushing the first block to obtain a third mixed powder; performing a second ball milling on the third mixed powder to obtain a fourth mixed powder; and performing a hot pressing sintering treatment on the fourth mixed powder.
[0006] The above method optimizes the performance of manganese-zinc ferrite by adjusting the molding process of manganese-zinc ferrite to achieve the purpose of homogenizing the components. In theory, it has an effect on improving the composition uniformity and material performance of manganese-zinc ferrite. However, through this simple process superposition, especially pre-sintering and then crushing, the pre-sintering temperature is low, and there is no good diffusion effect between the raw materials. It is easy to form uneven components during the crushing process. In addition, this multiple sintering and crushing will inevitably cause waste of raw materials and increase in costs during the later screening process. This method aims at the frequency characteristics and impedance performance of manganese-zinc ferrite. A manganese-zinc ferrite with high frequency and high impedance is obtained by dual improvements in preparation process and components, which is suitable for large-scale industrial promotion. Summary of the invention
[0007] The present invention aims to provide a low-loss, high-impedance manganese-zinc ferrite material and a preparation method thereof, which has a significant gain effect on the frequency characteristics, impedance performance and other properties of the manganese-zinc ferrite through improvements in related processes and raw materials.
[0008] Principle of this method: 1. The uniformity of material components has a very obvious effect on material properties. In the actual preparation process, the segregation and agglomeration of materials should be reduced as much as possible. In the present invention, the raw material powder and the auxiliary material powder are first granulated with PVA, then pre-sintered, and finally crushed. This is because there are differences in particle size and specific gravity between the auxiliary material and the raw material, which can easily cause uneven distribution during the mixing process. Granulation can be performed first, so that PVA can be coated with the powder. When cold pressing is performed afterwards, the distribution of the raw materials inside can be as uniform as possible. Finally, the mixed powder obtained after crushing is also uniform in composition; 2. Hot pressing and sintering can significantly reduce the sintering temperature of the material , vacuum hot pressing sintering is first carried out at low temperature, and then pressureless sintering in air atmosphere is carried out. This can reduce the sintering temperature and holding time of the material to a certain extent, and avoid long-term high temperature maintenance causing grain growth of the material. High-temperature hot pressing sintering is not carried out because the oxygen partial pressure is low under vacuum state, which will cause the oxide inside the material to deoxidize to form oxygen vacancies and reduce the impedance of the material; 3. The elements TiO2, Bi2O3, V2O5, Co2O3, MoO3, Nb2O5, CaCO3 and other elements in the auxiliary materials have the effect of inhibiting grain growth and reducing the sintering temperature respectively. Reasonable addition of auxiliary raw materials has a gain effect on improving the performance of the material.
[0009] The key points of this method are: 1. During the granulation process, the raw materials and auxiliary materials need to be distributed as evenly as possible, which requires that PVA can well cover the powder during the granulation process with PVA; 2. During the pre-sintering process, the sintering temperature and insulation time should be selected reasonably to avoid high density after sintering, which makes the raw materials difficult to crush; 3. The time during the sintering process should not be too long, and the temperature should not be too high to avoid abnormal growth of grains inside the material and uneven grain size.
[0010] The specific implementation scheme of a low-loss, high-impedance manganese-zinc ferrite material and a preparation method thereof according to the present invention is as follows:
[0011] Step S1: prepare raw materials and auxiliary materials in proportion
[0012] The raw materials are configured according to the molar ratio: Fe2O3: 47.5-49.5%, ZnO: 14.5-17.5%, MnO: 31.5-33%, and the auxiliary materials are configured according to the mass ratio of the raw materials: TiO2: 0.05-0.1%, Bi2O3: 0.001-0.004%, V2O5: 0.01-0.03%, Co2O3: 0.02-0.06%, MoO3: 0.03-0.05%, Nb2O5: 0.01-0.03%, CaCO3: 0.01-0.03%;
[0013] Step S2, obtaining a pre-block by granulation and pre-sintering
[0014] Mix Fe2O3, ZnO, MnO, TiO2, Bi2O3, V2O5, Co2O3, MoO3, Nb2O5, CaCO3 and 40-70% PVA solution and perform ball milling, the ball milling method is horizontal ball milling, the ball milling time is 20-50min, the ball milling speed is 100-150rpm, wherein the PVA content in the PVA solution is 3-5%;
[0015] The mixed slurry after ball milling is subjected to spray granulation, the water evaporation rate is 10-15Kg / h, the drying temperature is 200-240℃, and the obtained spherical powder particle size is 30-60μm;
[0016] The mixed spherical powder after granulation is subjected to cold pressing treatment, the cold pressing pressure is 20-40MPa, the holding time is 3-10min, and the relative density of the obtained green body is 20-35%;
[0017] The cold pressed block is pre-sintered at a sintering temperature of 700-900°C, a sintering holding time of 1-3h, and an air atmosphere;
[0018] Step S3, obtaining manganese-zinc ferrite by crushing and re-sintering
[0019] The pre-sintered pre-block is mechanically crushed, ball-milled, and sieved to obtain a secondary mixed powder, and the powder particle size D50 is required to be 0.2-1.2μm;
[0020] The crushed powder is subjected to a low-temperature vacuum hot-pressing sintering to obtain a precursor block, the sintering pressure is 30-50MPa, the sintering temperature is 500-700℃, and the holding time is 30-90min;
[0021] The precursor block is sintered in air without pressure to obtain manganese zinc ferrite, the sintering temperature is 1000-1200°C, and the insulation time is 1-3h.
[0022] Beneficial effects:
[0023] (1) The present invention designs a low-loss, high-impedance manganese-zinc ferrite material and a preparation method thereof, wherein the distribution of each element in the mixed powder can be uniform by first granulating PVA, then pre-sintering, and finally crushing, and finally the component uniformity of the material is improved during the sintering process;
[0024] (2) The present invention designs a low-loss, high-impedance manganese-zinc ferrite material and a preparation method thereof, which first performs vacuum hot pressing sintering at low temperature and then performs pressureless sintering in air atmosphere, thereby reducing the sintering temperature and the insulation time of the material, avoiding the growth of the grain size inside the material, and improving the performance of the material;
[0025] (3) The present invention designs a low-loss, high-impedance manganese-zinc ferrite material and a preparation method thereof. The selection of relevant auxiliary materials has obvious beneficial effects on improving the material properties and increasing the density of the material after sintering. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The present invention is a preparation flow chart of a low-loss, high-impedance manganese-zinc ferrite material and its preparation method. DETAILED DESCRIPTION
[0027] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0028] The embodiment of the present invention provides a low-loss, high-impedance manganese-zinc ferrite material and a preparation method thereof, the method mainly comprising the following steps:
[0029] Step S1: prepare raw materials and auxiliary materials in proportion
[0030] The raw materials are configured according to the molar ratio: Fe2O3, ZnO, MnO, and the auxiliary materials are configured according to the mass ratio of the raw materials: TiO2, Bi2O3, V2O5, Co2O3, MoO3, Nb2O5, CaCO3;
[0031] Step S2, obtaining a pre-block by granulation and pre-sintering
[0032] Fe2O3, ZnO, MnO, TiO2, Bi2O3, V2O5, Co2O3, MoO3, Nb2O5, CaCO3 and PVA solution were mixed and ball-milled;
[0033] The mixed slurry after ball milling is subjected to spray granulation;
[0034] The mixed spherical powder after granulation is cold pressed;
[0035] Pre-sintering the cold-pressed block;
[0036] Step S3, obtaining manganese-zinc ferrite by crushing and re-sintering
[0037] Mechanically crushing the pre-sintered precursor block;
[0038] The crushed powder is subjected to a low-temperature vacuum hot-pressing sintering to obtain a precursor block;
[0039] The precursor block is re-sintered in air without pressure to obtain manganese-zinc ferrite;
[0040] As an embodiment, the following content of the embodiments of the present invention gives several specific examples of the aforementioned low-loss, high-impedance manganese-zinc ferrite material and its preparation method, such as Example 1, Example 2, Example 3 and Examples 1-7 for comparison and explanation.
[0041] Embodiment 1:
[0042] Step S1: prepare raw materials and auxiliary materials in proportion
[0043] The raw materials are configured according to the molar ratio: Fe2O3: 55.5%, ZnO: 14.5%, MnO: 30%, and the auxiliary materials are configured according to the mass ratio of the raw materials: TiO2: 0.05%, Bi2O3: 0.001%, V2O5: 0.01%, Co2O3: 0.02%, MoO3: 0.03%, Nb2O5: 0.01%, CaCO3: 0.01%;
[0044] Step S2, obtaining a pre-block by granulation and pre-sintering
[0045] Fe2O3, ZnO, MnO, TiO2, Bi2O3, V2O5, Co2O3, MoO3, Nb2O5, CaCO3 and 40% PVA solution were mixed and ball-milled, the ball-milling method was horizontal ball-milling, the ball-milling time was 20 minutes, the ball-milling speed was 100 rpm, and the PVA content in the PVA solution was 3%;
[0046] The mixed slurry after ball milling was spray granulated, the water evaporation rate was 10Kg / h, the drying temperature was 200℃, and the obtained spherical powder particle size was 30μm;
[0047] The mixed spherical powder after granulation was subjected to cold pressing treatment, the cold pressing pressure was 20MPa, the holding time was 3min, and the relative density of the obtained green body was 20%;
[0048] The cold pressed block was pre-sintered at a sintering temperature of 700°C, a sintering holding time of 1h, and an air atmosphere;
[0049] Step S3, obtaining manganese-zinc ferrite by crushing and re-sintering
[0050] The pre-sintered pre-block is mechanically crushed, ball-milled, and sieved to obtain a secondary mixed powder, and the powder particle size D50 is required to be 0.2 μm;
[0051] The crushed powder is subjected to low-temperature vacuum hot pressing sintering to obtain a precursor block, with a sintering pressure of 30 MPa, a sintering temperature of 500 ° C, and a holding time of 30 min;
[0052] The precursor block is pressurelessly sintered in air to obtain manganese-zinc ferrite. The sintering temperature is 1000°C and the holding time is 1 hour.
[0053] Embodiment 2:
[0054] Step S1: prepare raw materials and auxiliary materials in proportion
[0055] The raw materials are configured according to the molar ratio: Fe2O3: 49.5%, ZnO: 17.5%, MnO: 33%, and the auxiliary materials are configured according to the mass ratio of the raw materials: TiO2: 0.1%, Bi2O3: 0.004%, V2O5: 0.03%, Co2O3: 0.06%, MoO3: 0.05%, Nb2O5: 0.03%, CaCO3: 0.03%;
[0056] Step S2, obtaining a pre-block by granulation and pre-sintering
[0057] Fe2O3, ZnO, MnO, TiO2, Bi2O3, V2O5, Co2O3, MoO3, Nb2O5, CaCO3 and 70% PVA solution were mixed and ball-milled in a horizontal ball milling manner for 50 minutes at a ball milling speed of 150 rpm, wherein the PVA content in the PVA solution was 5%;
[0058] The mixed slurry after ball milling was spray granulated, the water evaporation rate was 15Kg / h, the drying temperature was 240℃, and the obtained spherical powder particle size was 60μm;
[0059] The mixed spherical powder after granulation was subjected to cold pressing treatment, the cold pressing pressure was 40MPa, the holding time was 10min, and the relative density of the obtained green body was 35%;
[0060] The cold pressed block was pre-sintered at a sintering temperature of 900°C, a sintering holding time of 3h, and an air atmosphere;
[0061] Step S3, obtaining manganese-zinc ferrite by crushing and re-sintering
[0062] The pre-sintered pre-block is mechanically crushed, ball-milled, and sieved to obtain a secondary mixed powder, and the powder particle size D50 is required to be 1.2 μm;
[0063] The crushed powder is subjected to low-temperature vacuum hot pressing sintering to obtain a precursor block, with a sintering pressure of 50 MPa, a sintering temperature of 700 ° C, and a holding time of 90 min;
[0064] The precursor block is sintered in air without pressure to obtain manganese zinc ferrite. The sintering temperature is 1200°C and the holding time is 3 hours.
[0065] Embodiment 3:
[0066] Step S1: prepare raw materials and auxiliary materials in proportion
[0067] The raw materials are configured according to the molar ratio: Fe2O3: 49.5%, ZnO: 17.5%, MnO: 33%, and the auxiliary materials are configured according to the mass ratio of the raw materials: TiO2: 0.08%, Bi2O3: 0.003%, V2O5: 0.02%, Co2O3: 0.05%, MoO3: 0.04%, Nb2O5: 0.02%, CaCO3: 0.02%;
[0068] Step S2, obtaining a pre-block by granulation and pre-sintering
[0069] Fe2O3, ZnO, MnO, TiO2, Bi2O3, V2O5, Co2O3, MoO3, Nb2O5, CaCO3 and 60% PVA solution were mixed and ball-milled in a horizontal ball milling manner for 30 minutes at a ball milling speed of 120 rpm, wherein the PVA content in the PVA solution was 4%;
[0070] The mixed slurry after ball milling was spray granulated, the water evaporation rate was 12Kg / h, the drying temperature was 220℃, and the obtained spherical powder particle size was 50μm;
[0071] The mixed spherical powder after granulation was subjected to cold pressing treatment, the cold pressing pressure was 30MPa, the holding time was 5min, and the relative density of the obtained green body was 30%;
[0072] The cold pressed block is pre-sintered at a sintering temperature of 800°C, a sintering holding time of 2h, and an air atmosphere;
[0073] Step S3, obtaining manganese-zinc ferrite by crushing and re-sintering
[0074] The pre-sintered pre-block is mechanically crushed, ball-milled, and sieved to obtain a secondary mixed powder, and the powder particle size D50 is required to be 0.8 μm;
[0075] The crushed powder is subjected to a low-temperature vacuum hot-pressing sintering to obtain a precursor block, with a sintering pressure of 40 MPa, a sintering temperature of 600 ° C, and a holding time of 60 min;
[0076] The precursor block is pressurelessly sintered in air to obtain manganese-zinc ferrite. The sintering temperature is 1100°C and the holding time is 2h.
[0077] Comparative Example 1:
[0078] Step S1: prepare raw materials and auxiliary materials in proportion
[0079] The raw materials are configured according to the molar ratio: Fe2O3: 49.5%, ZnO: 17.5%, MnO: 33%, and the auxiliary materials are configured according to the mass ratio of the raw materials: TiO2: 0.08%, Bi2O3: 0.003%, V2O5: 0.02%, Co2O3: 0.05%, MoO3: 0.04%, Nb2O5: 0.02%, CaCO3: 0.02%;
[0080] Step S2, obtaining a pre-block by granulation and pre-sintering
[0081] Fe2O3, ZnO, MnO, TiO2, Bi2O3, V2O5, Co2O3, MoO3, Nb2O5, CaCO3 and 60% PVA solution were mixed and ball-milled in a horizontal ball milling manner for 30 minutes at a ball milling speed of 120 rpm, wherein the PVA content in the PVA solution was 4%;
[0082] The mixed slurry after ball milling was spray granulated, the water evaporation rate was 12Kg / h, the drying temperature was 220℃, and the obtained spherical powder particle size was 50μm;
[0083] The mixed spherical powder after granulation was subjected to cold pressing treatment, the cold pressing pressure was 30MPa, the holding time was 5min, and the relative density of the obtained green body was 30%;
[0084] The cold pressed block is pre-sintered at a sintering temperature of 800°C, a sintering holding time of 2h, and an air atmosphere;
[0085] Step S3, obtaining manganese-zinc ferrite by crushing and re-sintering
[0086] The pre-sintered pre-block is mechanically crushed, ball-milled, and sieved to obtain a secondary mixed powder, and the powder particle size D50 is required to be 0.8 μm;
[0087] The crushed powder is subjected to a low-temperature vacuum hot-pressing sintering to obtain a precursor block, with a sintering pressure of 40 MPa, a sintering temperature of 600 ° C, and a holding time of 60 min;
[0088] The precursor block is pressurelessly sintered in air to obtain manganese-zinc ferrite. The sintering temperature is 1100°C and the holding time is 2h.
[0089] Comparative Example 2:
[0090] Step S1: prepare raw materials and auxiliary materials in proportion
[0091] The raw materials are configured according to the molar ratio: Fe2O3: 49.5%, ZnO: 17.5%, MnO: 33%, and the auxiliary materials are configured according to the mass ratio of the raw materials: V2O5: 0.02%, Co2O3: 0.05%, MoO3: 0.04%, CaCO3: 0.02%;
[0092] Step S2, obtaining a pre-block by granulation and pre-sintering
[0093] Fe2O3, ZnO, MnO, V2O5, Co2O3, MoO3, CaCO3 and 60% PVA solution were mixed and ball-milled in a horizontal ball milling mode for 30 minutes at a ball milling speed of 120 rpm, wherein the PVA content in the PVA solution was 4%;
[0094] The mixed slurry after ball milling was spray granulated, the water evaporation rate was 12Kg / h, the drying temperature was 220℃, and the obtained spherical powder particle size was 50μm;
[0095] The mixed spherical powder after granulation was subjected to cold pressing treatment, the cold pressing pressure was 30MPa, the holding time was 5min, and the relative density of the obtained green body was 30%;
[0096] The cold pressed block is pre-sintered at a sintering temperature of 800°C, a sintering holding time of 2h, and an air atmosphere;
[0097] Step S3, obtaining manganese-zinc ferrite by crushing and re-sintering
[0098] The pre-sintered pre-block is mechanically crushed, ball-milled, and sieved to obtain a secondary mixed powder, and the powder particle size D50 is required to be 0.8 μm;
[0099] The crushed powder is subjected to a low-temperature vacuum hot-pressing sintering to obtain a precursor block, with a sintering pressure of 40 MPa, a sintering temperature of 600 ° C, and a holding time of 60 min;
[0100] The precursor block is pressurelessly sintered in air to obtain manganese-zinc ferrite. The sintering temperature is 1100°C and the holding time is 2h.
[0101] Comparative Example 3:
[0102] Step S1: prepare raw materials and auxiliary materials in proportion
[0103] The raw materials are configured according to the molar ratio: Fe2O3: 49.5%, ZnO: 17.5%, MnO: 33%, and the auxiliary materials are configured according to the mass ratio of the raw materials: TiO2: 0.08%, Bi2O3: 0.003%, V2O5: 0.02%, Co2O3: 0.05%, MoO3: 0.04%, Nb2O5: 0.02%, CaCO3: 0.02%;
[0104] Step S2, obtaining a pre-block by granulation and pre-sintering
[0105] Fe2O3, ZnO, MnO, TiO2, Bi2O3, V2O5, Co2O3, MoO3, Nb2O5 and CaCO3 were mixed and ball-milled in a horizontal ball mill with a ball milling time of 30 min and a ball milling speed of 120 rpm;
[0106] The mixed slurry after ball milling was spray granulated, the water evaporation rate was 12Kg / h, and the drying temperature was 220℃;
[0107] The mixed spherical powder after granulation was subjected to cold pressing treatment, the cold pressing pressure was 30MPa, the holding time was 5min, and the relative density of the obtained green body was 30%;
[0108] The cold pressed block is pre-sintered at a sintering temperature of 800°C, a sintering holding time of 2h, and an air atmosphere;
[0109] Step S3, obtaining manganese-zinc ferrite by crushing and re-sintering
[0110] The pre-sintered pre-block is mechanically crushed, ball-milled, and sieved to obtain a secondary mixed powder, and the powder particle size D50 is required to be 0.8 μm;
[0111] The crushed powder is subjected to a low-temperature vacuum hot-pressing sintering to obtain a precursor block, with a sintering pressure of 40 MPa, a sintering temperature of 600 ° C, and a holding time of 60 min;
[0112] The precursor block is pressurelessly sintered in air to obtain manganese-zinc ferrite. The sintering temperature is 1100°C and the holding time is 2h.
[0113] Comparative Example 4:
[0114] Step S1: prepare raw materials and auxiliary materials in proportion
[0115] The raw materials are configured according to the molar ratio: Fe2O3: 49.5%, ZnO: 17.5%, MnO: 33%, and the auxiliary materials are configured according to the mass ratio of the raw materials: TiO2: 0.08%, Bi2O3: 0.003%, V2O5: 0.02%, Co2O3: 0.05%, MoO3: 0.04%, Nb2O5: 0.02%, CaCO3: 0.02%;
[0116] Step S2, obtaining a pre-block by granulation and pre-sintering
[0117] Fe2O3, ZnO, MnO, TiO2, Bi2O3, V2O5, Co2O3, MoO3, Nb2O5, CaCO3 and 60% PVA solution were mixed and ball-milled in a horizontal ball milling manner for 30 minutes at a ball milling speed of 120 rpm, wherein the PVA content in the PVA solution was 4%;
[0118] The mixed slurry after ball milling was spray granulated, the water evaporation rate was 12Kg / h, the drying temperature was 220℃, and the obtained spherical powder particle size was 50μm;
[0119] The mixed spherical powder after granulation was subjected to cold pressing treatment, the cold pressing pressure was 30MPa, the holding time was 5min, and the relative density of the obtained green body was 30%;
[0120] The cold pressed block is pre-sintered at a sintering temperature of 800°C, a sintering holding time of 2h, and an air atmosphere;
[0121] Step S3, obtaining manganese-zinc ferrite by crushing and re-sintering
[0122] The pre-sintered pre-block is mechanically crushed, ball-milled, and sieved to obtain a secondary mixed powder, and the powder particle size D50 is required to be 0.8 μm;
[0123] The crushed powder is subjected to a low-temperature vacuum hot-pressing sintering to obtain a precursor block, with a sintering pressure of 40 MPa, a sintering temperature of 600 ° C, and a holding time of 60 min;
[0124] The precursor block is pressurelessly sintered in air to obtain manganese-zinc ferrite. The sintering temperature is 1100°C and the holding time is 6 hours.
[0125] Comparative Example 5:
[0126] Step S1: prepare raw materials and auxiliary materials in proportion
[0127] The raw materials are configured according to the molar ratio: Fe2O3: 49.5%, ZnO: 17.5%, MnO: 33%, and the auxiliary materials are configured according to the mass ratio of the raw materials: TiO2: 0.08%, Bi2O3: 0.003%, V2O5: 0.02%, Co2O3: 0.05%, MoO3: 0.04%, Nb2O5: 0.02%, CaCO3: 0.02%;
[0128] Step S2, obtaining a pre-block by granulation and pre-sintering
[0129] Fe2O3, ZnO, MnO, TiO2, Bi2O3, V2O5, Co2O3, MoO3, Nb2O5, CaCO3 and 60% PVA solution were mixed and ball-milled in a horizontal ball milling manner for 30 minutes at a ball milling speed of 120 rpm, wherein the PVA content in the PVA solution was 4%;
[0130] The mixed slurry after ball milling was spray granulated, the water evaporation rate was 12Kg / h, the drying temperature was 220℃, and the obtained spherical powder particle size was 50μm;
[0131] The mixed spherical powder after granulation was subjected to cold pressing treatment, the cold pressing pressure was 30MPa, the holding time was 5min, and the relative density of the obtained green body was 30%;
[0132] The cold pressed block is pre-sintered at a sintering temperature of 1200°C, a sintering holding time of 2h, and an air atmosphere;
[0133] Step S3, obtaining manganese-zinc ferrite by crushing and re-sintering
[0134] The pre-sintered pre-block is mechanically crushed, ball-milled, and sieved to obtain a secondary mixed powder, and the powder particle size D50 is required to be 0.8 μm;
[0135] The crushed powder is subjected to a low-temperature vacuum hot-pressing sintering to obtain a precursor block, with a sintering pressure of 40 MPa, a sintering temperature of 600 ° C, and a holding time of 60 min;
[0136] The precursor block is pressurelessly sintered in air to obtain manganese-zinc ferrite. The sintering temperature is 1100°C and the holding time is 2h.
[0137] Comparative Example 6:
[0138] Step S1: prepare raw materials and auxiliary materials in proportion
[0139] The raw materials are configured according to the molar ratio: Fe2O3: 49.5%, ZnO: 17.5%, MnO: 33%, and the auxiliary materials are configured according to the mass ratio of the raw materials: TiO2: 0.08%, Bi2O3: 0.003%, V2O5: 0.02%, Co2O3: 0.05%, MoO3: 0.04%, Nb2O5: 0.02%, CaCO3: 0.02%;
[0140] Step S2, obtaining a pre-block by granulation and pre-sintering
[0141] Fe2O3, ZnO, MnO, TiO2, Bi2O3, V2O5, Co2O3, MoO3, Nb2O5, CaCO3 and 60% PVA solution were mixed and ball-milled in a horizontal ball milling manner for 30 minutes at a ball milling speed of 120 rpm, wherein the PVA content in the PVA solution was 4%;
[0142] The mixed slurry after ball milling was spray granulated, the water evaporation rate was 12Kg / h, the drying temperature was 220℃, and the obtained spherical powder particle size was 50μm;
[0143] The mixed spherical powder after granulation was subjected to cold pressing treatment, the cold pressing pressure was 30MPa, the holding time was 5min, and the relative density of the obtained green body was 30%;
[0144] The cold pressed block is pre-sintered at a sintering temperature of 800°C, a sintering holding time of 2h, and an air atmosphere;
[0145] Step S3, obtaining manganese-zinc ferrite by crushing and re-sintering
[0146] The pre-sintered pre-block is mechanically crushed, ball-milled, and sieved to obtain a secondary mixed powder, and the powder particle size D50 is required to be 0.8 μm;
[0147] The crushed powder is subjected to low-temperature vacuum hot pressing sintering to obtain a precursor block, with a sintering pressure of 40 MPa, a sintering temperature of 1100°C, and a holding time of 60 min;
[0148] The precursor block is pressurelessly sintered in air to obtain manganese-zinc ferrite. The sintering temperature is 1100°C and the holding time is 2h.
[0149] Comparative Example 7:
[0150] Step S1: prepare raw materials and auxiliary materials in proportion
[0151] The raw materials are configured according to the molar ratio: Fe2O3: 49.5%, ZnO: 17.5%, MnO: 33%, and the auxiliary materials are configured according to the mass ratio of the raw materials: TiO2: 0.08%, Bi2O3: 0.003%, V2O5: 0.02%, Co2O3: 0.05%, MoO3: 0.04%, Nb2O5: 0.02%, CaCO3: 0.02%;
[0152] Step S2, obtaining a pre-block by granulation and pre-sintering
[0153] Fe2O3, ZnO, MnO, TiO2, Bi2O3, V2O5, Co2O3, MoO3, Nb2O5, CaCO3 and 60% PVA solution were mixed and ball-milled in a horizontal ball milling manner for 30 minutes at a ball milling speed of 120 rpm, wherein the PVA content in the PVA solution was 4%;
[0154] The mixed slurry after ball milling was spray granulated, the water evaporation rate was 12Kg / h, the drying temperature was 220℃, and the obtained spherical powder particle size was 50μm;
[0155] The mixed spherical powder after granulation was subjected to cold pressing treatment, the cold pressing pressure was 30MPa, the holding time was 5min, and the relative density of the obtained green body was 30%;
[0156] The cold pressed block is pre-sintered at a sintering temperature of 800°C, a sintering holding time of 2h, and an air atmosphere;
[0157] Step S3, obtaining manganese-zinc ferrite by crushing and re-sintering
[0158] The pre-sintered pre-block is mechanically crushed, ball-milled, and sieved to obtain a secondary mixed powder, and the powder particle size D50 is required to be 0.8 μm;
[0159] The crushed powder is sintered in air without pressure to obtain manganese-zinc ferrite. The sintering temperature is 1100°C and the insulation time is 2h.
[0160] Table 1:
[0161]
[0162] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 1 in Table 1, it can be found that the impedance reduction of Examples 1, 2, and 3 is significantly reduced compared with Comparative Example 1, which shows that when the iron content in the manganese-zinc ferrite is higher than the set value, the iron-rich formula has a small amount of Fe 2+ exists, forming Fe in the crystal lattice 2+ -Fe 3+ Electron pair, electron in Fe 2+ , Fe 3+The transition between them makes the impedance of the material decrease; from the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 2 in Table 1, it can be found that the relative density, initial magnetic permeability and impedance of Examples 1, 2 and 3 are all lower than those of Comparative Example 2, which shows that TiO2, Bi2O3 and Nb2O5 have a beneficial effect on the material. A certain content of TiO2, Bi2O3, Nb2O5 and other auxiliary materials can increase the cutoff frequency of the material and reduce the high-frequency power loss; from the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 3 in Table 1, it can be found that the relative density, initial magnetic permeability and impedance of Examples 1, 2 and 3 are all lower than those of Comparative Example 2, which shows that TiO2, Bi2O3 and Nb2O5 have a beneficial effect on the material. A certain content of TiO2, Bi2O3, Nb2O5 and other auxiliary materials can increase the cutoff frequency of the material and reduce the high-frequency power loss. The relative density, initial magnetic permeability and impedance of Comparative Example 3 are all reduced, which shows that after PVA is not added in the granulation process, the uniformity of the material cannot be guaranteed because the material powders themselves cannot bond to each other, and different degrees of segregation will occur, affecting the performance of the material; from the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 4 in Table 1, it can be found that the relative density, initial magnetic permeability and impedance of Examples 1, 2, 3 compared with Comparative Example 4 are all reduced, which shows that when the holding time in the pressureless sintering process during re-sintering is too long, it will cause abnormal growth of grains, resulting in partial crystallization. The size of the particles is uneven, which affects the performance of the material. From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 5 in Table 1, it can be found that the primary sintered blocks of Examples 1, 2, 3 and Comparative Example 5 cannot be broken, which shows that during the pre-sintering process, the sintering temperature should not be too high, as too high a temperature will lead to an increase in the density of the material and cause difficulties in subsequent processing. From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 6 in Table 1, it can be found that the impedance of Examples 1, 2, 3 and Comparative Example 6 decreases significantly, which shows that when the sintering temperature is too high during the primary low-temperature hot pressing sintering process, it will cause The material is formed in advance, and a large number of oxygen vacancies are formed inside the material. During the subsequent short-term air atmosphere sintering, oxygen filling cannot be completely completed, and there will still be residual oxygen vacancies, resulting in a decrease in material performance. From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 7 in Table 1, it can be found that the impedance of Examples 1, 2, 3 compared with Comparative Example 7 is significantly reduced, which shows that when low-temperature vacuum hot pressing sintering is not performed, the material cannot be completely sintered and dense by simply relying on the subsequent re-sintering. At this time, the temperature required for sintering the material is higher than the set temperature, which causes an increase in internal defects in the material and a decrease in material performance.
[0163] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution, which should be included in the scope of the claims of the present invention.
Claims
1. A method for preparing a low-loss, high-impedance manganese-zinc ferrite material, characterized in that: include: Allocate raw materials and auxiliary materials in proportion; The pre-block is obtained by granulation and pre-sintering; Manganese-zinc ferrite is obtained by crushing and re-sintering; Wherein, the step of configuring the raw materials and auxiliary materials in proportion includes: The raw materials are configured according to the molar ratio: Fe2O3, ZnO, MnO, and the auxiliary materials are configured according to the mass ratio of the raw materials: TiO2, Bi2O3, V2O5, Co2O3, MoO3, Nb2O5, CaCO3; The step of obtaining the pre-block by granulation and pre-sintering comprises: Fe2O3, ZnO, MnO, TiO2, Bi2O3, V2O5, Co2O3, MoO3, Nb2O5, CaCO3 and PVA solution were mixed and ball-milled; The mixed slurry after ball milling is subjected to spray granulation; The mixed spherical powder after granulation is cold pressed; Pre-sintering the cold-pressed block; The step of obtaining manganese-zinc ferrite by crushing and re-sintering comprises: Mechanically crushing the pre-sintered precursor block; The crushed powder is subjected to low-temperature vacuum hot pressing sintering to obtain a precursor block; the precursor block is subjected to air pressureless sintering to obtain manganese-zinc ferrite.
2. The method for preparing a low-loss, high-impedance manganese-zinc ferrite material according to claim 1, characterized in that: The steps of configuring the raw materials: Fe2O3, ZnO, MnO in molar proportion, and configuring the auxiliary materials: TiO2, Bi2O3, V2O5, Co2O3, MoO3, Nb2O5, CaCO3 according to the mass ratio of the raw materials include: The raw materials are configured according to the molar ratio: Fe2O3: 49.5%, ZnO: 17.5%, MnO: 33%; the auxiliary materials are configured according to the mass ratio of the raw materials: TiO2: 0.05-0.1%, Bi2O3: 0.001-0.004%, V2O5: 0.01-0.03%, Co2O3: 0.02-0.06%, MoO3: 0.03-0.05%, Nb2O5: 0.01-0.03%, CaCO3: 0.01-0.03%.
3. The method for preparing a low-loss, high-impedance manganese-zinc ferrite material according to claim 1, characterized in that: The step of mixing Fe2O3, ZnO, MnO, TiO2, Bi2O3, V2O5, Co2O3, MoO3, Nb2O5, CaCO3 and PVA solution for ball milling comprises: Fe2O3, ZnO, MnO, TiO2, Bi2O3, V2O5, Co2O3, MoO3, Nb2O5, CaCO3 and 40-70% PVA solution are mixed and ball-milled in a horizontal ball mill for 20-50 minutes at a ball milling speed of 100-150 rpm, wherein the PVA content in the PVA solution is 3-5%.
4. The method for preparing a low-loss, high-impedance manganese-zinc ferrite material according to claim 1, characterized in that: The step of spray granulating the mixed slurry after ball milling comprises: The mixed slurry after ball milling is subjected to spray granulation, the water evaporation rate is 10-15Kg / h, the drying temperature is 200-240°C, and the obtained spherical powder particle size is 30-60μm.
5. The method for preparing a low-loss, high-impedance manganese-zinc ferrite material according to claim 1, characterized in that: The step of cold pressing the granulated mixed spherical powder comprises: The mixed spherical powder after granulation is cold pressed, the cold pressing pressure is 20-40MPa, the holding time is 3-10min, and the relative density of the obtained green body is 20-35%.
6. The method for preparing a low-loss, high-impedance manganese-zinc ferrite material according to claim 1, characterized in that: The step of pre-sintering the cold-pressed block comprises: The cold pressed block is pre-sintered at a sintering temperature of 700-900°C, a sintering holding time of 1-3h, and an air atmosphere.
7. The method for preparing a low-loss, high-impedance manganese-zinc ferrite material according to claim 1, characterized in that: The step of mechanically crushing the pre-sintered pre-block includes: mechanically crushing the pre-sintered pre-block, ball milling, and sieving to obtain a secondary mixed powder, and the powder particle size D50 is required to be 0.2-1.2 μm.
8. The method for preparing a low-loss, high-impedance manganese-zinc ferrite material according to claim 1, characterized in that: The step of subjecting the crushed powder to low-temperature vacuum hot pressing sintering to obtain a precursor block comprises: The crushed powder is subjected to low-temperature vacuum hot pressing sintering to obtain a precursor block, the sintering pressure is 30-50MPa, the sintering temperature is 500-700℃, and the holding time is 30-90min.
9. The method for preparing a low-loss, high-impedance manganese-zinc ferrite material according to claim 1, characterized in that: The step of re-sintering the precursor block in air without pressure to obtain manganese-zinc ferrite comprises: The precursor block is sintered in air without pressure to obtain manganese zinc ferrite, the sintering temperature is 1000-1200°C, and the insulation time is 1-3h.
Citation Information
Patent Citations
A manganese-zinc ferrite and its preparation method
CN108147805B
A high-frequency, high-impedance iron-poor manganese-zinc ferrite and its preparation method
CN111233452B
High-frequency high-impedance iron-poor manganese-zinc ferrite and preparation method thereof
CN111233452A